2013
DOI: 10.1096/fj.12-222687
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight‐induced alterations in cerebral artery vasoconstrictor, mechanical, and structural properties: implications for elevated cerebral perfusion and intracranial pressure

Abstract: Evidence indicates that cerebral blood flow is both increased and diminished in astronauts on return to Earth. Data from ground-based animal models simulating the effects of microgravity have shown that decrements in cerebral perfusion are associated with enhanced vasoconstriction and structural remodeling of cerebral arteries. Based on these results, the purpose of this study was to test the hypothesis that 13 d of spaceflight [Space Transportation System (STS)-135 shuttle mission] enhances myogenic vasoconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 59 publications
3
56
0
Order By: Relevance
“…In MCA, we have observed the opposite effect: an increase of RyR1 expression correlated with the suspected increase of blood loading. Very recently, it has been demonstrated that vasoconstriction was decreased in basilar arteries from mice exposed to μG during spaceflight [41]. However, in HU animals our results are all clearly in favor of an increase in vascular reactivity.…”
Section: Role Of Ryr In Hu and Microgravitysupporting
confidence: 44%
“…In MCA, we have observed the opposite effect: an increase of RyR1 expression correlated with the suspected increase of blood loading. Very recently, it has been demonstrated that vasoconstriction was decreased in basilar arteries from mice exposed to μG during spaceflight [41]. However, in HU animals our results are all clearly in favor of an increase in vascular reactivity.…”
Section: Role Of Ryr In Hu and Microgravitysupporting
confidence: 44%
“…Animal studies applying mice experiencing real spaceflight [28] and tailsuspended hindlimb unweighting (HU) rats [10,18,24,34,35] also give support to the involvement of microgravity-induced vascular responsiveness adaptations in postflight orthostatic intolerance. However, mechanisms underlying the aforementioned abnormal vascular responsiveness have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…During a long duration space mission, astronauts are expected to have greater exposure to cosmic radiation at a steady, but low, dose rate, compared to SPE radiation that delivers a high dose in shorter time periods [32]. Other space flight conditions/stressors, such as elevated cabin carbon dioxide concentrations, may also be a confounding contributor to changes in cerebral blood flow and ICP [33, 34]. …”
Section: Discussionmentioning
confidence: 99%